2020
DOI: 10.1177/1096348019896086
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Childhood Engagement in the Context of Hospitality Service Failure Evaluation

Abstract: Marketing research shows that customer relationship management can reduce consequences of service failures. The question is how long a former customer engagement can still have an effect on a current critical incident. In extreme cases, this means whether and how interactions between company and customer during childhood can still influence the effects of a service failure. This article proposes that engagement with a company during childhood (childhood engagement) can affect later perceptions of the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…In contrast, when customers feel that the cause of the failure is uncontrollable, they put less blame on the service providers. Papen et al (2020) also indicated that controllability has a significant moderating effect on the relationship between disappointment with the organization and intention to repurchase. Accordingly, the following hypothesis is proposed for testing in this present study: H3: Controllability moderates the relationship between brand attitude and behavioral intention in the context of national carrier's service failure.…”
Section: H2: Stability Moderates the Relationship Between Brand Attitmentioning
confidence: 94%
“…In contrast, when customers feel that the cause of the failure is uncontrollable, they put less blame on the service providers. Papen et al (2020) also indicated that controllability has a significant moderating effect on the relationship between disappointment with the organization and intention to repurchase. Accordingly, the following hypothesis is proposed for testing in this present study: H3: Controllability moderates the relationship between brand attitude and behavioral intention in the context of national carrier's service failure.…”
Section: H2: Stability Moderates the Relationship Between Brand Attitmentioning
confidence: 94%
“…But the question is for how long an instance of CE may influence a current critical incident, such as whether and how company-customer interactions during childhood may continue to influence the effects of service failure. Papen et al (2020) posit that engagement with a company during childhood (childhood engagement) can affect subsequent perceptions of the relationship. Through an experiment with 152 participants, their study reveals that perceived controllability and childhood engagement moderate the effect of disappointment on repurchase intention.…”
mentioning
confidence: 99%